2016
DOI: 10.17815/cd.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

Age and Group-driven Pedestrian Behaviour: from Observations to Simulations

Abstract: The development of pedestrian simulation systems requires the acquisition of empirical evidences about human behaviour for sake of model validation. In this framework, the paper presents the results of an on field observation of pedestrian behaviour in an urban crowded walkway. The research was aimed at testing the potentially combined effect of ageing and grouping on speed and proxemic behaviour. In particular, we focused on dyads, as the most frequent type of groups in the observed scenario. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The influential parameters were selected based on analysis of existing studies among those that resulted important when it comes to research of pedestrian behavior. Many studies have shown that children's behavior in traffic is influenced by their age, gender [21,23,24] control of inhibitors, parental expectations and beliefs [25], parental supervision [26], the complexity of the situation [19], the distraction of attention [27,28], and various development and other parameters that are not measurable in real traffic conditions.…”
Section: Influential Parameters and Field-testing Methodologymentioning
confidence: 99%
“…The influential parameters were selected based on analysis of existing studies among those that resulted important when it comes to research of pedestrian behavior. Many studies have shown that children's behavior in traffic is influenced by their age, gender [21,23,24] control of inhibitors, parental expectations and beliefs [25], parental supervision [26], the complexity of the situation [19], the distraction of attention [27,28], and various development and other parameters that are not measurable in real traffic conditions.…”
Section: Influential Parameters and Field-testing Methodologymentioning
confidence: 99%
“…Broken groups can regroup to keep the unity [9,28]. When individuals meet groups, singles are statistically walking faster and are more likely to adjust their routes [6,10]. Stationary groups act as obstacles [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of social groups can influence the dynamics of pedestrian crowds. Social groups often move slower and reduce the walking speed of the pedestrians [3,8,9,10]. However, Manenti et al [11] observed that group members can walk faster than individuals in high density scenarios.…”
Section: Introductionmentioning
confidence: 99%